FUNGSI AKAL DALAM PEMIKIRAN PEMBAHARUAN MODERN ISLAM (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2022)
In the utilization of reason, man still does not fully use reason in accordance with his position and function. In fact, the problems that arise are increasingly complex so that the role of reason is needed. This study aims to combine the thoughts of Harun Nasution and Nurkholish Madjid on the Function of Reason in Islamic Modern Renewal Thinking. Type of library research (Library research). The form of data used is qualitative. The second source of data is primary data, in the form of all the works of Harun Nasution and Nurkholish Madjid related to the Function of Reason. While secondary data is in the form of books, journals, the internet and others related to research. Methods of data collection through documentation. Descriptive and comparative data analysis techniques. The results showed that in addition to similarities, positions also have a role related to differences in the function of reason according to Harun Nasution and Nurkholish Madjid. The position of reason according to Aaron Nasution as a basis or intermediary. Meanwhile, Nurkholish Madjid is positioned as a tool or means. It is from this position of reason that it will determine the function of reason. According to Harun Nasution and Nurkholish Madjid, reason is to function for thinking power that is able to seek truth and science so that it is able to progress in accordance with the times. Meanwhile, the difference in the function of reason from the two is caused by facing different problems. Harun Nasution explained the function of reason on the basis of a renewal of the mindset towards religion which is very closely related to dogma (Divinity and Society). Meanwhile, Nurkholish Madjid, the function of reason as a tool or means in the renewal of mindsets that are much related to the fields of Science and Science (Society). Keywords: Reason, Islamic Modern Thought, Harun Nasution, Nurkholish Madjid